2009
DOI: 10.1111/j.1463-1326.2008.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diabetic hypertension

Abstract: Insulin resistance and hyperglycaemia combine to make hypertension more prevalent in the type 2 diabetic patient. Blood pressure goals below those for the non-diabetic subject have been shown to be more effective in lowering mortality and cardiovascular events in the diabetic patient. To achieve these goals in most cases, three to five antihypertensives from different therapeutic groups need to be utilized. Suppression of the renin-angiotensin system (RAS) with angiotensin-converting enzyme inhibitors, angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…For example, in a study conducted between 2005 and 2006 in 26 countries, the overall BP control rate was 33.6% in men and 30.6% in women and was lower in diabetic as compared to non-diabetic patients [23]. Another study carried out in the United States by Grant et al also reported similar prevalence of BP control (33%) [24].…”
Section: Discussionmentioning
confidence: 59%
“…For example, in a study conducted between 2005 and 2006 in 26 countries, the overall BP control rate was 33.6% in men and 30.6% in women and was lower in diabetic as compared to non-diabetic patients [23]. Another study carried out in the United States by Grant et al also reported similar prevalence of BP control (33%) [24].…”
Section: Discussionmentioning
confidence: 59%
“…[23][24][25][26] Initiation or addition of an antihypertensive agent with a different pharmacologic action can result in SBP reductions of 10 to 15 mm Hg. 27 Multiple antihypertensive drugs with different and complementary pharmacologic actions can be used to successfully treat hypertension in patients with diabetes. 27 Additionally, fixed-dose combinations may increase compliance compared with freedose combinations through simplification of treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…27 Multiple antihypertensive drugs with different and complementary pharmacologic actions can be used to successfully treat hypertension in patients with diabetes. 27 Additionally, fixed-dose combinations may increase compliance compared with freedose combinations through simplification of treatment regimens. Two meta-analyses demonstrated that fixed-dose combination therapy for hypertension increased compliance; in one meta-analysis, compliance was increased by 29%, 28 and in another, the risk of noncompliance was decreased by 24%.…”
Section: Discussionmentioning
confidence: 99%
“…Further lowering of BP in these circumstances could lead to adverse events. Patients with diabetes tend to have depressed heart rate variability and autonomic dysfunction and frequently are already taking beta blockers (Bell 2009). Particularly if their glucose levels are not well controlled, they also may become fluid depleted and hypovolemic during periods of concurrent high temperature and high ozone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes itself increases the risk of hypertension and orthostatic hypotension because of chronic autonomic dysregulation, endothelial dysfunction, atherosclerosis, and dysregulation of fluid balance and the renin-angiotensin system (Pop-Busui 2010; Ribeiro-Oliveira et al 2008). Common medications, such as beta blockers, may further block appropriate compensatory autoregulatory vascular responses (Bell 2009). We have shown that elevated PM pollution exposure adds to autonomic dysregulation, endothelial dysfunction (O’Neill et al 2005), and inflammation (Dubowsky et al 2006), particularly in persons with diabetes.…”
mentioning
confidence: 99%